Potassium solubilization by bacterial strain in waste mica - Meena, VS; Maurya, BR; Bahadur, Indra (Bangladesh Journal of Botany, 2015)
The release of K from waste mica (muscovite and biotite) was tested with 4 K-solubilizing isolates collected from maize rhizosphere, for 7, 14 and 21 days of incubation at 28 ± 2°C. K-solubilization by different bacterial isolates showed significant change on muscovite and biotite powder supplemented plates and the amount of K released varied from 1.28 - 46.75 ?g/ml. The soluble K contents in all isolated treatments were significantly higher than control. Herein, isolate KSB2 had higher K-solubilization ability when compared with other isolates (KSB1, KSB3 and KSB4) in vitro DOI: http://dx.doi.org/10.3329/bjb.v43i2.21680 Bangladesh J. Bot. 43(2): 235-237, 2014 (September)